(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present paper is an analysis of the use of wordslexis to tell about a world whichmesmerizes readers draws them into it with ease. The author does away with the conventional way ofusing the lexical items she innovates. She goes beyond the set of choices available and coins new words.There is coming together as well as splitting of words in unusual ways.